A proteção de dados pessoais na pesquisa em saúde - Feitosa, Lukas Darien Dias (2023)
The increasing relevance of personal data in contemporary socioeconomic logic, coupled with the growth of information and communication technologies' processing capabilities, has necessitated the development of a legal framework for the protection of personal data capable of adapting to the technical and legal reality of personal data processing. In Brazil, heavily inspired by the European experience, the Brazilian General Data Protection Law (LGPD, in Portuguese) was approved with the purpose of regulating the processing of personal data, impacting to varying degrees all activities dealing with such information. In addition, Constitutional Amendment 115 was approved at the end of 2022, which, among other issues, modified the list of fundamental rights enshrined in Article 5 of the Federal Constitution, including the right to the protection of personal data. In this context, health research experiences an imminent need to reorganize its practices, given its substantial handling of sensitive personal data, which is subject to heightened legal protection. Therefore, this study aimed to analyze the impact of the new legislation on health research activities, discussing its constitutional foundations, the process of establishing the legislation in Brazil, and the process of adapting the activities to the demands of the LGPD. In this regard, the foundations of the development of personal data protection as a fundamental right were discussed, emphasizing informational self-determination as an essential element in this process. It was demonstrated how the LGPD was implemented in Brazil and how it broadly and generically regulates activities involving the processing of personal data within the national territory. Subsequently, the direct impact of the LGPD on health research activities was examined, discussing the provisions of the legislation and their relationship with the stages of the academic health production process in the Brazilian context, highlighting the potential obstacles and adaptation needs required by the law. Finally, a reflection was made on how research institutions can reorganize themselves to comply with the determinations of the LGPD, particularly considering the perspective of self-regulation, given the emphasis placed by the LGPD on the need for data processing agents to autonomously analyze their own security and personal data protection needs and establish governance practices and work processes in accordance with the legislation's requirements. In conclusion, it was determined that health research activities need to have a specific understanding of their data security obligations, and research institutions have the responsibility to enable researchers to analyze and respond to these demands. Additionally, research institutions are tasked with providing an adequate technical environment and adopting their own governance policies for health research activities.